Show da Luna: uma ferramenta didática no ensino de ciências - Gonzaga, Daniela Goulart Leles (2017)
Television, as well as other means of communication, develop sophisticated forms of sensory, emotional and rational communication that allow to relate the different areas of knowledge. In this way, the cartoons and movies have been occupying space within the educational process, because they function as didactic tools in this process. Through the starting question "Will the Luna® Show, associated with the conceptualization and use of experiments facilitate a better learning in Science Teaching in the elementary school (6th to 9th grade) of Educandário Cruzeiro do Sul, in Duque de Caxias (RJ)?. The design presents a theme that can be associated with the curricular contents presented in the classroom. The objective of this work was to elaborate an Educational Product that corresponds to an Activity Book based on the analysis of 30 episodes of the above mentioned design. It presents a relationship with Science Teaching in Basic Education with a proposal to contribute through a set of interconnected activities, planned for the science teacher who work in this segment of education, to transmit the curricular content step by step, organized according to the goals they want to achieve for their students' learning. The work was grounded on the Russian Proximal Development Zone Theory (ZPD) by Lev S. Vygotsky. It is a qualitative research, with applied nature aiming to generate knowledge about the series of drawings in question. Being focused on the reality of the classrooms and the participation of the researched in the activities suggested in the Activity Book, one can observe characteristics of Action-research in this work. The Educational Product was validated by 10 (ten) teachers who work in the Public and Private Networks of Rio de Janeiro and Metropolitan Region, who work in classes of Elementary School (6th to 9th grade) and tested by 65 students of the same class segment of Educandário Cruzeiro do Sul in Duque de Caxias (RJ) during the academic year of 2016. As data collection, two questionnaires were developed, one (1) aimed at the participating teachers and another one for the students who delivered the Term of Free and Informed Consent (TCLE) signed by the legal guardian. The analysis of the data was done in a systemic and individual way, and was therefore favorable to the approval of the Activity Book for the most part, concluding that, despite being a production aimed at serving children between 3 and 6 years of age, their approach is related to the curricular contents of the discipline of Sciences applied in classrooms. However, it is suggested that a new approach to the Educational Product in an investigative way, to sharpen reflection and criticality of students is applied, since many of these found the design with a child profile for their age group.